The Role of Free Tissue Transfer in the Management of Chronic Frontal Sinus Osteomyelitis. (14th December 2018) - Rimmer, Ryan A.; Duffy, Alexander N.; Knops, Alexander M.; Rabinowitz, Mindy R.; Koszewski, Ian J.; Rosen, Marc R.; Ortlip, Timothy; Heffelfinger, Ryan N.; Garcia, Hermes G.; Evans, James J.; Nyquist, Gurston G.; Curry, Joseph M.
Abstract : Objectives/Hypothesis: Chronic frontal sinus infection is managed with a combination of medical and surgical interventions. Frontal bone osteomyelitis due to recurrent infection following trauma or prior open surgery may require more significant debridement. Free tissue transfer may allow for extensive debridement with replacement of tissue, and definitive eradication of osteomyelitis. Study Design: Retrospective chart review. Methods: Patients undergoing free flap obliteration of the frontal sinus for frontal bone osteomyelitis at a single institution were included in the study. Clinical, radiologic, and surgical data were collected. Surgeries before and after free flap obliteration were compared by Wilcoxon signed rank test. Results: Fifteen patients were identified; however, one patient had less than 6 months of follow‐up and was excluded from analysis. Of the remaining 14 patients, mean follow‐up duration was 26 months (range, 6–120 months). Mean number of surgeries prior to free flap was 3.7 (range, 1–8 surgeries). Free flap obliteration resolved chronic frontal sinusitis in all patients. Two patients experienced postoperative infection, and the overall complication rate was 29%. Eight patients underwent cranioplasty (six immediate, two delayed) without complication. All patients received planned courses of postoperative antibiotics. A statistically significant decrease in the number of surgeries after free flap obliteration was observed P ≤ .01). Conclusions: Extensive debridement followed by free tissue transfer and antibiotics offers a definitive treatment for complicated, recurrent frontal osteomyelitis. Simultaneous cranioplasty provides immediate protective and aesthetic benefit without complication. Consideration should be given for free tissue transfer and cranioplasty earlier in the algorithm for treatment of refractory frontal sinus osteomyelitis. Level of Evidence: 4 Laryngoscope, 129:1497–1504, 2019